Inequality and Team Performance - Felix Kölle; Dirk Sliwka; Nannan Zhou (Verein für Socialpolitik, 2010)
We investigate the effects of wealth inequality on the incentives to contribute to a public good or a team output when agents are inequity averse. We show that inequality may increase total output when it favors the more able agents. Moreover, the more inequity averse the agents, the larger should be the inequality in wealth if total output is to be maximized.
Keywords: M50; M52; D31; 330; Public good; team incentives; inequity aversion; inequality; wage setting